Investigations into the safety and immunogenicity of a killed oral cholera vaccine developed in Viet Nam - Trach D.D; Cam P.D; Ke N.T; Rao M.R; Dinh D.; Hang P.V; Hung N.V; Canh D.G; Thiem V.D; Naficy A.; Ivanoff B.; Svennerholm A-M; et al. (The World Health Organization, 2002)
OBJECTIVE: To evaluate a killed oral cholera vaccine produced in Viet Nam, and to compare the Vietnamese vaccine with one that is licensed internationally. METHOD: Two-dose regimens of a locally produced, bivalent, anti-O1, anti-O139 killed oral whole-cell cholera vaccine (biv-WC) and of a commercially available, monovalent (anti-O1) oral recombinant B subunit-killed whole-cell cholera vaccine (rBS-WC) were compared in two trials in Viet Nam. In the first trial, 144 adults were randomized to biv-WC with or without buffer, rBS-WC with buffer, or placebo without buffer. In the second, 103 children aged 1-12 years were randomized to biv-WC without buffer, rBS-WC with buffer, or placebo without buffer. FINDINGS: No regimen was associated with significant side-effects. In adults, ca 60% of recipients of either vaccine exhibited at least fourfold serum anti-O1 vibriocidal antibody responses and ca 40% of recipients of biv-WC demonstrated anti-O139 vibriocidal responses. Both anti-O1 (ca 90% in each vaccine groupand anti-O139 (68% in the biv-WC group) vibriocidal responses occurred more frequently in children. The responses to biv-WC were unaffected by the receipt of buffer. CONCLUSION: It was concluded that biv-WC was safe and immunogenic, that it could be administered without buffer, and that it could elicit robust immune responses even in children, for whom the risk of endemic cholera is highest.